MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN KOMPETENSI GURU PENDIDIKAN DASAR DI MASA PANDEMI COVID-19 - Moh Trisamanta; Mohammad Zalmi Kahardani; Medya Appriliansyah; Trifiana Tiodora (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The important educational situations, which used to work on the nature ofinstructive outcomes, were greatly influenced by the nature of theirpresentation. Together so that the implementation of schooling can be carriedout properly, educators are also required to have good performance. However, towards the beginning of 2020, the world was shocked by the Covid(Coronavirus) pandemic which attacks the human respiratory system andbecomes the most important health emergency on the planet. The infection,which started in Wuhan, China, first entered Indonesia on the 2nd, 2020. Thepandemic caused all face-to-face learning in schools and colleges during thispandemic to be temporarily closed and replaced by distance learning or onlinelearning. The principal's leadership plays a very important role in realizingquality and will affect the nature of teaching in schools. The purpose of thisresearcher is the leadership management of school principals in building thecompetence of basic education teachers during the covid-19 pandemic. Thetype of research used is literature study research. The principal has a veryimportant role in improving the quality or performance of teachers. This isbecause the quality of education is strongly influenced by the learning processcarried out by the teacher (teacher). Therefore, principals need to domanagement to design a leadership strategy. The principal's leadershipstrategy in improving the quality of education during the Covid-19 pandemicincludes 3 (three) strategic management processes including strategicformulation or planning, strategic implementation and strategic evaluation